The University in Africa and Democratic Citizenship - Luescher-Mamashela, Thierry M. (African Minds, 2012)
Whether and how higher education in Africa contributes to democratisation beyond producing the professionals that are necessary for developing and sustaining a modern political system, remains an unresolved question. This report, then, represents an attempt to address the question of whether there are university specific mechanisms or pathways by which higher education contributes to the development of democratic attitudes and behaviours among students, and how these mechanisms operate and relate to politics both on and off campus. The research contained in this report shows that the potential of a university to act as training ground for democratic citizenship is best realised by supporting students' exercise of democratic leadership on campus. This, in turn, develops and fosters democratic leadership in civil society. Thus, the university's response to student political activity, student representation in university governance and other aspects of extra-curricular student life needs to be examined for ways in which African universities can instil and support democratic values and practices. Encouraging and facilitating student leadership in various forms of on-campus political activity and in a range of student organisations emerges as one of the most promising ways in which African universities can act as training grounds for democratic citizenship. The project on which this report is based forms part of a larger study on Higher Education and Democracy in Africa, undertaken by the Higher Education Research and Advocacy Network in Africa (HERANA). HERANA is coordinated by the Centre for Higher Education Transformation in South Africa.